Makna Aksi Sosial dalam Praktik Buka Pintu Ya Lail: Studi Etnografi Living Hadis Masyarakat Kp. Kemanisan, Serang–Banten - Sulton Kholid; Muhammad Alif (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study examines the meaning of social action in the practice of opening the door of Ya Lail in the marriage tradition of the people of Kampung Kemisan, Serang-Banten, with a living hadith approach. The tradition of opening  the door of Ya Lail is understood by the community as a hereditary custom that contains the value of manners, respect, and prayer in the wedding procession. This research aims to uncover the meaning of social action in the practice and its conformity with the values of the hadith of the Prophet Muhammad صلى الله عليه وسلم.  This study uses a qualitative method with an ethnographic approach, through field observation, interviews, and documentation. Data analysis was carried out with the framework of social action and the living hadith approach. The study's results show that the practice of opening the door of Ya Lail is a meaningful social action, in which the symbolic dialogue and the act of opening the door reflect the manners of asking for permission, politeness, and respect. From the perspective of living hadith, this tradition actualizes the hadith's values regarding social manners and the formation of morals, even though it is not always presented in the form of hadith texts. This study concludes that the tradition of opening the door of Ya Lail is a living form of hadith that is alive and contextual in the life of the people of Kemanisan Village. Keywords: social action, opening the door of Ya Lail, living hadith, ethnography. Abstrak Penelitian ini mengkaji makna aksi sosial dalam praktik buka pintu Ya Lail pada tradisi pernikahan masyarakat Kampung Kemanisan, Serang–Banten, dengan pendekatan living hadis. Tradisi buka pintu Ya Lail dipahami oleh masyarakat sebagai adat turun-temurun yang mengandung nilai adab, penghormatan, dan doa dalam prosesi pernikahan. Penelitian ini bertujuan untuk mengungkap makna tindakan sosial dalam praktik tersebut serta kesesuaiannya dengan nilai-nilai hadis Nabi Muhammad ﷺ. Penelitian ini menggunakan metode kualitatif dengan pendekatan etnografi, melalui observasi lapangan, wawancara, dan dokumentasi. Analisis data dilakukan dengan kerangka aksi sosial dan pendekatan living hadis. Hasil penelitian menunjukkan bahwa praktik buka pintu Ya Lail merupakan tindakan sosial yang bermakna, di mana dialog simbolik dan pembukaan pintu mencerminkan adab meminta izin, kesopanan, dan penghormatan. Dalam perspektif living hadis, tradisi ini mengaktualisasikan nilai-nilai hadis tentang adab sosial dan pembentukan akhlak, meskipun tidak selalu dihadirkan dalam bentuk teks hadis. Penelitian ini menyimpulkan bahwa tradisi buka pintu Ya Lail merupakan bentuk living hadis yang hidup dan kontekstual dalam kehidupan masyarakat Kampung Kemanisan. Kata kunci: aksi sosial, buka pintu Ya Lail, living hadis, etnografi.